(untitled) (KULT_online, 2011)
Since the mid-1990s, representations of the Holocaust in the visual arts, literature, and popular culture have undergone a paradigm shift, becoming both more transgressive and more scandalous. How and why should artistic and cultural representations of the Holocaust arouse today precisely the kind of emotional provocation that is peculiar to its subject matter? These are the main questions that the artist testimonies and scholarly essays collected by Sophia Komor and Susanne Rohr in The Holocaust, Art, and Taboo: Transatlantic Exchanges on the Ethics and Aesthetics of Representation, invite their readers to grapple with—in utterly engaging and thought-provoking ways.